(untitled) (Journal of Asian Development Studies, 2018)
The paper characterises women in the informal sector in the peri-urban settlement by way of a case study of Ruwa. Qualitative methodologies, with a little mix of the positivist approach, were adopted. Forty women engaged in informal sector operations ranging from street (off-plot) and on-plot activities were adopted. Challenges that these operators faced were noted as relating to elements (rain, wind, and the sun), service provision, marketing of products, and regulatory forces. It is recommended that all stakeholders dissect common issues and formulate poverty-tolerant strategies that are accommodative of the plight and challenges of the peri-urban women. Critical to note is strength of the will-power and resilience most of the respondents displayed. The most important thing is perhaps of harnessing on this intrinsic virtue to nurture and develop it for local developmental gain.